2020
DOI: 10.1039/c9gc04348a
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine activities of phthalate alternatives; assessing the safety profile of furan dicarboxylic acid esters using a panel of human cell based reporter gene assays

Abstract: Ensuring non-regrettable substitution of fossil derived chemicals by biobased alternatives using human cell based reporter gene assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Not always the technical benefits which are encountered by replacing PTA by FDCA to make PEF instead of PET are encountered but when FDCA becomes an economically competitive bulk monomer those other outlets will also be very interesting. Many other FDCA containing polyesters have been reported as well as polyamides, polyurethanes, thermoset resins [ 7 , 8 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] and references therein] as well as plasticizers to replace phthalate-based compounds [ 70 , 71 , 72 ].…”
Section: How the Technologies Developed Over Timementioning
confidence: 99%
“…Not always the technical benefits which are encountered by replacing PTA by FDCA to make PEF instead of PET are encountered but when FDCA becomes an economically competitive bulk monomer those other outlets will also be very interesting. Many other FDCA containing polyesters have been reported as well as polyamides, polyurethanes, thermoset resins [ 7 , 8 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ] and references therein] as well as plasticizers to replace phthalate-based compounds [ 70 , 71 , 72 ].…”
Section: How the Technologies Developed Over Timementioning
confidence: 99%
“…3−7 Yet, despite the long history of FDCA and its related polymers, some properties have only recently attracted attention. Examples are studies into the toxicity of FDCA and its related diesters, 8 into the enzymatic hydrolysis of PEF, 9 or into the (bio)degradability of PEF. 10 Surprisingly, to the best of our knowledge, we could not find any investigation into the weathering stability of FDCA-based polyesters.…”
mentioning
confidence: 99%
“…Very recently the endocrine disruptor activity of furan dicarboxylic acid esters has been assessed and compared to that of phthalates. 31 BPA has been shown to have estrogenic activity and to be an antagonist for androgenic receptor. 32 Evidence was found that BPA can also disrupt thyroid hormone action.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Currently, there is no report on the evaluation of endocrine activity in furanic diols, and thus, the current work fills an important knowledge gap. Very recently the endocrine disruptor activity of furan dicarboxylic acid esters has been assessed and compared to that of phthalates …”
Section: Resultsmentioning
confidence: 99%